Effects of preoperative endoscopic pneumatic balloon dilatation on postoperative achalasia symptoms after Heller esophageal myotomy plus Dor fundoplication - Öter, Volkan; Bostancı, Erdal Birol; Karaman, Kerem; Sümer, Fatih; Özer, İlter (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Currently, forceful endoscopic pneumatic balloon dilatation (PBD), laparoscopic Heller myotomy (LHM) with or without an anti-reflux procedure, and peroral endoscopic myotomy are the preferred treatment options for achalasia. The aim of the present study was to retrospectively compare postoperative outcomes after LHM plus Dor fundoplication (DF) between patients who underwent prior endoscopic balloon dilatation and those who did not. Materials and Methods: Sixty-five patients who underwent HM+DF between January 2008 and December 2016 were retrospectively analyzed. Of these, 45 had a history of endoscopic PBD. Pre- and postoperative achalasia symptoms, including weight loss, dysphagia, heartburn, and regurgitation, were evaluated using the Eckardt score. Results: Fifty (76.9%) patients underwent laparoscopic surgery and 15 (23.1%) underwent open surgery. When patients were compared according to the presence of preoperative endoscopic PBD, no significant difference were observed in terms of age, sex, preoperative lower esophageal sphincter pressure, operation time, hospitalization period, and follow-up period (p>0.05). The mean Eckardt score at the first postoperative year was significantly lower than the preoperative Eckardt score (4.51±1.8 vs. 0.52±0.7; p Conclusion: HM+DF is an effective procedure in relieving achalasia symptoms as a first-line therapy as well as in individuals unresponsive to repeated endoscopic PBDs. Cite this article as: Öter V, Bostancı EB, Karaman K, Sümer F, Özer İ. The effects of preoperative endoscopic pneumatic balloon dilatation on postoperative achalasia symptoms after Heller’s esophageal myotomy plus Dor fundoplication. Turk J Gastroenterol 2018; 29: 543-8.